Distribution of serotypes and antimicrobial resistance of Streptococcus pneumoniae strains isolated in Brazil from 1988 to 1992. - Sessegolo, J F (1994)
Forty-two serotypes were identified among 288 Streptococcus pneumoniae strains isolated from patients living in Brazil. Serotyping was determined by the capsular typing test (Quellung reaction). Types 14 (10.4%), 6B (9.8%), 23F (8.0%), 5 (7.3%), 19F (6.9%), 6A (6.0%), and 1 and 4 (4.6%) were the most commonly identified strains. Two hundred twenty (76.4%) of the strains were of serotypes that are included in the 23-valent pneumococcal polysaccharide vaccine. If vaccine-related serotypes are also considered, the proportions of coverage in the vaccine are 82.3% (if type 6B alone is added) and 85.7% (if all the vaccine-related types are considered to be cross-protecting). Decreased susceptibility to penicillin, which was identified by using the 1-microgram oxacillin disk method as a screening test, was detected in 70 (26.7%) strains. The MICs of nine antimicrobial agents were determined by using the procedures recommended by the National Committee for Clinical Laboratory Standards. Seventy (35.9%) of the strains were resistant to tetracycline, 57 (29.2%) were resistant to sulfamethoxazole-trimethoprim, 3 (1.5%) were resistant to rifampin, 2 (0.80%) were resistant to penicillin, and 1 (0.5%) was resistant to chloramphenicol. The two penicillin-resistant strains were also resistant to or had decreased susceptibilities to cephalosporins. Forty-seven (17.9%) of the strains were intermediately resistant to penicillin, 17 (8.7%) were intermediately resistant to tetracycline, 13 (6.7%) were intermediately resistant to chloramphenicol, 12 (6.1%) were intermediately resistant to erythromycin, and 6 (3.1%) were intermediately resistant to rifampin.